Undergraduate research in the global context: models and practices for high-quality mentoring. Issue 1 (1st January 2022) - Allocco, Amy L.; Vandermaas-Peeler, Maureen; Hall, Eric; Ketcham, Caroline; Idris, Mussa; Hamel, Jennifer A.; (Sandy) Marshall, David J.
ABSTRACT: By participating in faculty-mentored undergraduate research in global (domestic and international) contexts, students may integrate global learning, cultural humility, problem-solving, and ethical engagement with community partners while also developing foundational research knowledge and skills. We utilize an ecological framework to describe institutional supports and interrelationships between faculty mentors and students in our institutional context and highlight salient mentoring practices and models that facilitate collaboration and student learning within and across environments. Through four descriptive case studies, faculty mentors describe the rich cultural contexts in which the research occurs; elucidate the salient mentoring practices utilized to support students' personal and intellectual development; discuss constellations of mentors spanning different institutions, communities, and countries; and identify key institutional supports within the ecological framework. Each case highlights pedagogies and identifies practices that may be applied to a variety of research programs.